Preparation method of nano lithium iron phosphate composite positive electrode material

By double-layer coating of carbon and aluminum fluoride on lithium iron phosphate, the surface structure and position energy distribution are improved, and the structural collapse problem of lithium iron phosphate positive electrode material under high temperature or overcharge conditions is solved, and the circulation stability is improved , and consistency, suitable for mass production and extends the cycle life of lithium-ion batteries.

CN119191250APending Publication Date: 2024-12-27CHONGQING CITY VOCATIONAL COLLEGE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411153790.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-21
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing lithium iron phosphate positive electrode material is prone to collapse under high temperature or overcharge conditions, has poor circulation stability, and the solid phase process is simple but the consistency is poor, the liquid phase process is complex and the mass production is difficult.

Method used

Using the preparation method of nano-lithium iron phosphate composite positive electrode material, by first coating carbon on lithium iron phosphate and then coating aluminum fluoride, the surface structure and position energy distribution are changed, the diffusion rate of lithium ions is increased and iron is suppressed. Ion dissolution improves cycling stability.

Benefits of technology

It achieves good cycle stability and consistency of lithium iron phosphate positive electrode material, extends the cycle life of lithium-ion batteries, and reduces the preparation cost, making it suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005004339510000091
    Figure BDA0005004339510000091
Patent Text Reader

Abstract

The invention discloses a preparation method of a nano lithium iron phosphate composite positive electrode material, and relates to the technical field of lithium battery positive electrode materials, lithium iron phosphate is synthesized by adopting a self-heating evaporation liquid phase, external heat does not need to be provided, the preparation cost is reduced, the process is simple, materials are uniformly mixed, the product consistency is good, and the method is suitable for large-scale production; according to the invention, the lithium iron phosphate is coated by two layers, the first layer is coated by carbon, and the second layer is coated by aluminum fluoride, so that the prepared lithium iron phosphate positive electrode material has good cycle stability, and the cycle life of a lithium ion battery is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical field:

[0001] The invention relates to the technical field of lithium battery positive electrode materials, and in particular to a method for preparing a nano lithium iron phosphate composite positive electrode material. Background technology:

[0002] Lithium iron phosphate is a lithium-ion battery electrode material with the chemical formula LiFePO4, which is mainly used in various lithium-ion batteries. Because lithium iron phosphate has a stable PO bond, it is difficult to decompose. Even under high temperature or overcharge conditions, the structure will not collapse. It has good cycle performance and safety, so it has broad application prospects.

[0003] The preparation of lithium iron phosphate is mainly divided into two types: solid phase method and liquid phase method. The solid phase method includes high temperature solid phase reaction method, carbon thermal reduction method, microwave synthesis method, mechanical alloying method, and the liquid phase method includes liquid phase coprecipitation method, sol-gel method, hydrothermal synthesis method, etc. The solid phase method is the most commonly used method for preparing electrode materials because of its simple process and easy industrialization. The carbon thermal reduction method is the most common solid phase method. The carbon thermal reduction method uses cheap trivalent iron to reduce to divalent iron, and at the same time makes the pyrolyzed carbon coated on the lithium iron phosphate to enhance the conductivity, which can be said to kill two birds with one stone. The biggest feature of the liquid phase preparation is the addition of solvents. Taking the hydrothermal method as an example, water is used as a solvent in a sealed pressure vessel, and the raw materials are chemically reacted under high temperature and high pressure conditions. After filtering, washing, and drying, a nano precursor is obtained, and finally lithium iron phosphate is obtained after high temperature calcination.

[0004] From the perspective of the process flow alone, the solid-phase method is simple and suitable for large-scale production, but the materials are not mixed evenly and the particle size distribution range is wide, resulting in poor product consistency. The advantage of the liquid-phase method is uniform mixing and good product consistency, but the process is complex, the reaction conditions are high, and mass production is difficult. Summary of the invention:

[0005] The technical problem to be solved by the present invention is to provide a method for preparing a nano-lithium iron phosphate composite positive electrode material. By preparing nano-lithium iron phosphate and coating carbon and aluminum fluoride on the nano-lithium iron phosphate in sequence, a new type of lithium battery positive electrode material is prepared, and it shows good cycle stability.

[0006] The technical problem to be solved by the present invention is achieved by adopting the following technical solutions:

[0007] A method for preparing a nano lithium iron phosphate composite positive electrode material comprises the following preparation steps:

[0008] (1) weighing a lithium source, an iron source, and a phosphorus source in proportion, dissolving them in water, controlling the molar ratio of lithium, iron, and phosphorus elements to be (1.05-1.1):1:1, then adding concentrated sulfuric acid, adjusting the pH value of the solution to 3-5, and obtaining a mixed solution;

[0009] (2) adding a carbon source to the mixed solution prepared in step (1) under stirring, and evaporating the mixture by autothermal heating to obtain a solid precursor;

[0010] (3) heating the precursor to 600-800° C. under inert gas protection, sintering, cooling, crushing, and screening to obtain carbon-coated lithium iron phosphate;

[0011] (4) adding aluminum fluoride to water and dispersing by ultrasonication to obtain an aluminum fluoride solution;

[0012] (5) adding the aluminum fluoride solution prepared in step (4) into the carbon-coated lithium iron phosphate prepared in step (3) in the form of a spray, mixing evenly, heating to 300-500° C. under the protection of an inert gas for sintering, and cooling to obtain an aluminum fluoride-carbon-coated lithium iron phosphate positive electrode material.

[0013] The lithium source is one or more of lithium carbonate, lithium hydroxide, lithium acetate and lithium nitrate.

[0014] The iron source is one or more of ferric chloride, ferric hydroxide and ferric nitrate.

[0015] The phosphorus source is one or more of phosphoric acid, diammonium phosphate, and ammonium phosphate.

[0016] The carbon source is one or more of glucose, sucrose, starch and β-cyclodextrin.

[0017] The concentration of the concentrated sulfuric acid is 98 wt %.

[0018] The amount of the carbon source used is such that the carbon content in the final positive electrode material product reaches 0.5-3%.

[0019] The amount of aluminum fluoride used is such that the aluminum fluoride content in the final positive electrode material product reaches 0.05-0.5%.

[0020] The inert gas is one of nitrogen, argon and helium.

[0021] The heating rate of the sintering is 5-15°C / min.

[0022] Preparation principle: Lithium source, iron source and phosphorus source will spontaneously generate heat after adding carbon source under strong acidic and strong oxidizing conditions. The heat generated evaporates the water in the system to obtain a solid precursor; the precursor is sintered to form carbon-coated lithium iron phosphate, and then aluminum fluoride is used to secondary coat the carbon-coated lithium iron phosphate to obtain aluminum fluoride-carbon-coated lithium iron phosphate. The present invention changes the surface structure of lithium iron phosphate, optimizes the surface potential energy distribution state of lithium iron phosphate, improves the diffusion rate of lithium ions, and can effectively inhibit the dissolution of iron ions in the electrolyte, prevent the collapse of the positive electrode material structure, and thus improve the cycle stability of the lithium iron phosphate positive electrode material.

[0023] The present invention also provides a method for preparing a carbon source, by using the carbon source to replace glucose, sucrose, starch, and β-cyclodextrin as the carbon source, thereby achieving the technical effect of further optimizing the charge and discharge rate performance of the prepared lithium iron phosphate positive electrode material.

[0024] The carbon source is methyl pivalate-O-sucrose, and the preparation method thereof is as follows: dissolving sucrose in ethyl acetate, then adding chloromethyl pivalate and triethylamine, keeping the temperature under reflux for reaction, stopping the reaction after all the chloromethyl pivalate reacts, concentrating under reduced pressure to recover ethyl acetate, washing the obtained concentrate with ethanol, filtering by suction, and drying.

[0025] The molar ratio of the sucrose, chloromethyl pivalate and triethylamine is 1:1:1.

[0026] By controlling the molar ratio to allow one hydroxyl group in sucrose to participate in the reaction, modified sucrose was obtained and used as a carbon source. The study found that the carbon particles produced by thermal decomposition of the carbon source in an inert atmosphere can be evenly distributed between lithium iron phosphate grains and coated on the surface of the grains, inhibiting the growth of lithium iron phosphate grains, controlling the morphology of lithium iron phosphate grains, and making lithium iron phosphate have better cycle stability.

[0027] The beneficial effects of the present invention are:

[0028] (1) The present invention adopts self-heating evaporation liquid phase to synthesize lithium iron phosphate, which does not require external heat, reduces the preparation cost, and has a simple process, uniform material mixing, good product consistency, and a primary particle size of 50-70nm, which is suitable for large-scale production.

[0029] (2) The present invention adopts a two-layer coating method for lithium iron phosphate, the first layer is carbon coating, and the second layer is aluminum fluoride coating, so that the prepared lithium iron phosphate positive electrode material has good cycle stability, thereby extending the cycle life of the lithium ion battery. Specific implementation method:

[0030] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further described below in conjunction with specific embodiments.

[0031] Sucrose was purchased from Nanjing Chemical Reagent Co., Ltd.

[0032] Glucose was purchased from Nanjing Chemical Reagent Co., Ltd.

[0033] β-Cyclodextrin was purchased from Zhengzhou Kangyuan Chemical Products Co., Ltd.

[0034] Example 1

[0035] (1) lithium acetate, ferric chloride and phosphoric acid were weighed in proportion and dissolved in water to control the molar ratio of lithium, iron and phosphorus to be 1.05:1:1, and then 98 wt % concentrated sulfuric acid was added to adjust the pH value of the solution to 4 to obtain a mixed solution;

[0036] (2) adding sucrose to the mixed solution prepared in step (1) under stirring, and evaporating by autothermal heating to obtain a solid precursor;

[0037] (3) heating the precursor to 700° C. at a heating rate of 5° C. / min under nitrogen protection for 5 h, cooling, crushing, and screening to obtain carbon-coated lithium iron phosphate;

[0038] (4) adding aluminum fluoride to water and dispersing by ultrasonication to obtain an aluminum fluoride solution;

[0039] (5) Adding the aluminum fluoride solution prepared in step (4) into the carbon-coated lithium iron phosphate prepared in step (3) in the form of a spray, mixing evenly, heating to 500° C. at a heating rate of 10° C. / min under inert gas protection, sintering for 5 h, and cooling to obtain an aluminum fluoride-carbon-coated lithium iron phosphate positive electrode material.

[0040] The amount of sucrose added is such that the carbon content in the final positive electrode material product reaches 2%, and the amount of aluminum fluoride added is such that the aluminum fluoride content in the final positive electrode material product reaches 0.25%.

[0041] Example 2

[0042] (1) lithium nitrate, ferric hydroxide and phosphoric acid were weighed in proportion and dissolved in water to control the molar ratio of lithium, iron and phosphorus to be 1.05:1:1, and then 98 wt % concentrated sulfuric acid was added to adjust the pH value of the solution to 5 to obtain a mixed solution;

[0043] (2) adding sucrose to the mixed solution prepared in step (1) under stirring, and evaporating by autothermal heating to obtain a solid precursor;

[0044] (3) heating the precursor to 800° C. at a heating rate of 5° C. / min under nitrogen protection for 6 h, cooling, crushing, and screening to obtain carbon-coated lithium iron phosphate;

[0045] (4) adding aluminum fluoride to water and dispersing by ultrasonication to obtain an aluminum fluoride solution;

[0046] (5) Adding the aluminum fluoride solution prepared in step (4) into the carbon-coated lithium iron phosphate prepared in step (3) in the form of a spray, mixing evenly, heating to 500° C. at a heating rate of 5° C. / min under inert gas protection, sintering for 4 h, and cooling to obtain an aluminum fluoride-carbon-coated lithium iron phosphate positive electrode material.

[0047] The amount of sucrose added is such that the carbon content in the final positive electrode material product reaches 2%, and the amount of aluminum fluoride added is such that the aluminum fluoride content in the final positive electrode material product reaches 0.35%.

[0048] Example 3

[0049] (1) lithium carbonate, iron nitrate and ammonium phosphate were weighed in proportion and dissolved in water to control the molar ratio of lithium, iron and phosphorus to be 1.1:1:1, and then 98 wt % concentrated sulfuric acid was added to adjust the pH value of the solution to 4 to obtain a mixed solution;

[0050] (2) adding glucose to the mixed solution prepared in step (1) under stirring, and evaporating by autothermal heating to obtain a solid precursor;

[0051] (3) heating the precursor to 700° C. at a heating rate of 10° C. / min under nitrogen protection for 5 h, cooling, crushing, and screening to obtain carbon-coated lithium iron phosphate;

[0052] (4) adding aluminum fluoride to water and dispersing by ultrasonication to obtain an aluminum fluoride solution;

[0053] (5) Adding the aluminum fluoride solution prepared in step (4) into the carbon-coated lithium iron phosphate prepared in step (3) in the form of a spray, mixing evenly, heating to 450° C. at a heating rate of 10° C. / min under inert gas protection, sintering for 3 h, and cooling to obtain an aluminum fluoride-carbon-coated lithium iron phosphate positive electrode material.

[0054] The amount of starch added is such that the carbon content in the final positive electrode material product reaches 2.5%, and the amount of aluminum fluoride added is such that the aluminum fluoride content in the final positive electrode material product reaches 0.25%.

[0055] Example 4

[0056] (1) lithium nitrate, ferric nitrate and ammonium dihydrogen phosphate were weighed in proportion and dissolved in water to control the molar ratio of lithium, iron and phosphorus to be 1.1:1:1, and then 98 wt % concentrated sulfuric acid was added to adjust the pH value of the solution to 3 to obtain a mixed solution;

[0057] (2) adding β-cyclodextrin to the mixed solution prepared in step (1) under stirring, and evaporating by autothermal heating to obtain a solid precursor;

[0058] (3) heating the precursor to 800° C. at a heating rate of 10° C. / min under nitrogen protection for 8 h, cooling, crushing, and screening to obtain carbon-coated lithium iron phosphate;

[0059] (4) adding aluminum fluoride to water and dispersing by ultrasonication to obtain an aluminum fluoride solution;

[0060] (5) Adding the aluminum fluoride solution prepared in step (4) into the carbon-coated lithium iron phosphate prepared in step (3) in the form of a spray, mixing evenly, heating to 450° C. at a heating rate of 5° C. / min under inert gas protection, sintering for 3 h, and cooling to obtain an aluminum fluoride-carbon-coated lithium iron phosphate positive electrode material.

[0061] The amount of β-cyclodextrin added is such that the carbon content in the final positive electrode material product reaches 1.5%, and the amount of aluminum fluoride added is such that the aluminum fluoride content in the final positive electrode material product reaches 0.5%.

[0062] Example 5

[0063] Preparation of Methyl Pivalate-O-Sucrose:

[0064] Dissolve sucrose in ethyl acetate, then add chloromethyl pivalate and triethylamine, the molar ratio of sucrose, chloromethyl pivalate and triethylamine is 1:1:1, keep warm and react under reflux, stop the reaction after all the chloromethyl pivalate reacts, concentrate under reduced pressure to recover ethyl acetate, wash the obtained concentrate with ethanol, filter and dry.

[0065] The sucrose in Example 1 was replaced with methyl pivalate-O-sucrose as the carbon source to obtain Example 5.

[0066] (1) lithium acetate, ferric chloride and phosphoric acid were weighed in proportion and dissolved in water to control the molar ratio of lithium, iron and phosphorus to be 1.05:1:1, and then 98 wt % concentrated sulfuric acid was added to adjust the pH value of the solution to 4 to obtain a mixed solution;

[0067] (2) adding methyl pivalate-O-sucrose to the mixed solution prepared in step (1) under stirring, and evaporating by autothermal heating to obtain a solid precursor;

[0068] (3) heating the precursor to 700° C. at a heating rate of 5° C. / min under nitrogen protection for 5 h, cooling, crushing, and screening to obtain carbon-coated lithium iron phosphate;

[0069] (4) adding aluminum fluoride to water and dispersing by ultrasonication to obtain an aluminum fluoride solution;

[0070] (5) Adding the aluminum fluoride solution prepared in step (4) into the carbon-coated lithium iron phosphate prepared in step (3) in the form of a spray, mixing evenly, heating to 500° C. at a heating rate of 10° C. / min under inert gas protection, sintering for 5 h, and cooling to obtain an aluminum fluoride-carbon-coated lithium iron phosphate positive electrode material.

[0071] The amount of methyl pivalate-O-sucrose added is such that the carbon content in the final positive electrode material product reaches 2%, and the amount of aluminum fluoride added is such that the aluminum fluoride content in the final positive electrode material product reaches 0.25%.

[0072] Comparative Example

[0073] The aluminum fluoride coating step in Example 1 was removed to obtain a comparative example.

[0074] (1) lithium acetate, ferric chloride and phosphoric acid were weighed in proportion and dissolved in water to control the molar ratio of lithium, iron and phosphorus to be 1.05:1:1, and then 98 wt % concentrated sulfuric acid was added to adjust the pH value of the solution to 4 to obtain a mixed solution;

[0075] (2) adding sucrose to the mixed solution prepared in step (1) under stirring, and evaporating by autothermal heating to obtain a solid precursor;

[0076] (3) Under nitrogen protection, the temperature is raised to 700° C. at a heating rate of 5° C. / min, and the precursor is sintered for 5 h, cooled, crushed, and sieved to obtain carbon-coated lithium iron phosphate.

[0077] The amount of sucrose added is such that the carbon content in the final positive electrode material product reaches 2%.

[0078] The lithium iron phosphate positive electrode materials prepared in Examples 1-5 and the comparative example were respectively used as positive electrode active materials, and the metal lithium sheet was used as the negative electrode. The positive electrode sheet was composed of positive electrode active materials, acetylene black, and PVDF in a mass ratio of 80:10:10, Celgard2400 membrane was used as a separator, and 1 mol / L LiPF6 was used as an electrolyte (the solvent used ethylene carbonate and diethyl carbonate in a volume ratio of 1:1), and button batteries were assembled. The battery test system of Shenzhen Xinwei Company was used for testing at room temperature, and the test voltage was 2.5-4.2V. The test results are shown in Table 1.

[0079] Table 1 Cyclic stability of lithium iron phosphate cathode materials

[0080]

[0081] It can be seen from Table 1 that the lithium iron phosphate positive electrode materials prepared in Examples 1-5 of the present invention have good cycle stability, while the cycle stability of the comparative example is significantly reduced due to the lack of aluminum fluoride coating.

[0082] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A method for preparing a nano lithium iron phosphate composite positive electrode material, characterized in that: The method comprises the following preparation steps: (1) weighing a lithium source, an iron source, and a phosphorus source in proportion, dissolving them in water, controlling the molar ratio of lithium, iron, and phosphorus elements to be (1.05-1.1):1:1, then adding concentrated sulfuric acid, adjusting the pH value of the solution to 3-5, and obtaining a mixed solution; (2) adding a carbon source to the mixed solution prepared in step (1) under stirring, and evaporating the mixture by autothermal heating to obtain a solid precursor; (3) heating the precursor to 600-800° C. under inert gas protection, sintering, cooling, crushing, and screening to obtain carbon-coated lithium iron phosphate; (4) adding aluminum fluoride to water and dispersing by ultrasonication to obtain an aluminum fluoride solution; (5) adding the aluminum fluoride solution prepared in step (4) into the carbon-coated lithium iron phosphate prepared in step (3) in the form of a spray, mixing evenly, heating to 300-500° C. under the protection of an inert gas for sintering, and cooling to obtain an aluminum fluoride-carbon-coated lithium iron phosphate positive electrode material.

2. The method for preparing the nano-lithium iron phosphate composite positive electrode material according to claim 1, characterized in that: The lithium source is one or more of lithium carbonate, lithium hydroxide, lithium acetate and lithium nitrate.

3. The method for preparing the nano-lithium iron phosphate composite positive electrode material according to claim 1, characterized in that: The iron source is one or more of ferric chloride, ferric hydroxide and ferric nitrate.

4. The method for preparing the nano-lithium iron phosphate composite positive electrode material according to claim 1, characterized in that: The phosphorus source is one or more of phosphoric acid, diammonium phosphate, and ammonium phosphate.

5. The method for preparing the nano-lithium iron phosphate composite positive electrode material according to claim 1, characterized in that: The carbon source is one or more of glucose, sucrose, starch and β-cyclodextrin.

6. The method for preparing the nano-lithium iron phosphate composite positive electrode material according to claim 1, characterized in that: The concentration of the concentrated sulfuric acid is 98 wt %.

7. The method for preparing the nano-lithium iron phosphate composite positive electrode material according to claim 1, characterized in that: The amount of the carbon source used is such that the carbon content in the final positive electrode material product reaches 0.5-3%.

8. The method for preparing the nano-lithium iron phosphate composite positive electrode material according to claim 1, characterized in that: The amount of aluminum fluoride used is such that the aluminum fluoride content in the final positive electrode material product reaches 0.05-0.5%.

9. The method for preparing the nano-lithium iron phosphate composite positive electrode material according to claim 1, characterized in that: The inert gas is one of nitrogen, argon and helium.

10. The method for preparing the nano-lithium iron phosphate composite positive electrode material according to claim 1, characterized in that: The heating rate of the sintering is 5-15°C / min.